2013
DOI: 10.5146/tjpath.2014.01266
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal autopsy evaluation of 2150 autopsies in the Çukurova region of turkey

Abstract: Objective: We aimed to document the reasons of perinatal deaths in a large autopsy series performed in our institute, which is a reference center in the Çukurova region of Turkey. Material and Method:The study included 2150 autopsies performed between January 2000 and December 2012at our institute. Diagnoses were categorized according to the detected pathologies; congenital malformations were detailed based on systems. Results:A pathology was detected in 1619 of 2150 (73.3%) autopsies. Congenital malformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This is likely a considerable underestimate given lack of NGS at that time. Infants with recognizable genetic disorders have disproportionately longer hospitalizations and more frequent neonatal death[15–20]. …”
Section: Monogenic Diseases: Neonatal Impact and Incidencementioning
confidence: 99%
“…This is likely a considerable underestimate given lack of NGS at that time. Infants with recognizable genetic disorders have disproportionately longer hospitalizations and more frequent neonatal death[15–20]. …”
Section: Monogenic Diseases: Neonatal Impact and Incidencementioning
confidence: 99%
“…Of 23,910 recorded infant deaths, 66% were in the neonatal period, of which the leading cause was congenital malformations, deformations, and chromosomal abnormalities (20.8%) . Recognizable genetic disorders are disproportionately represented in infants with longer hospitalizations and more frequent neonatal death (Cunniff et al 1995;Yoon et al 1997;Zlotogora et al 2003;McCandless et al 2004;Simpson et al 2010;Acikalin et al 2014). …”
Section: Impact and Incidence Of Monogenic Diseasesmentioning
confidence: 99%
“…Based on Hakverdi et al's report, 36 of 274 cases (22.5%) were associated with musculoskeletal anomalies [20]. In Acikalin et al's study, 2150 fetal autopsies were reported and 97 of 2150 (8.3%) cases had musculoskeletal anomalies [21]. Thus, as there is no available data to compare the frequencies of SDs, our series is limited on the skeletal dysplasias, and discusses intensive genetic, radiologic and morphologic features.…”
Section: Discussionmentioning
confidence: 84%
“…ACH and hypochondroplasia dysplasias not only exhibit phenotypic but also genetic features. Ninety-nine percent of ACH dysplasias have two common FGFR3 gene mutations in p.Gly380Arg amino acid substitutions and, 10% of ACH is caused by p.Asn540Lys which is typical for hypochondroplasias [21]. However, 7% of hypochondroplasia cases are shown to have p.Gly380Arg mutation [23].…”
Section: Discussionmentioning
confidence: 97%